Proton-controlled mechanism for coupling among proton production/consumption reactions in CaCO3-oversaturated waters or calcifying organism-inhabited seawaters - Ichikawa, Kazuhiko (European Journal of Chemistry, 2010)
The CaCO3-oversaturated weakly basic water at around pH=8 was proved by the novel simple equations (e.g. log [Ca2+] = -2pH -logPCO2 + 9.94) derived from material energetics and proton-controlled mechanism for coupling among proton/hydroxide production/consumption reactions (e.g. CaCO3 + H+↔HCO3- + Ca2+) in equilibrium with atmospheric carbon dioxide. The cyclic/oscillating variation between pH=8.3 and 8.0 for marine calcifying organism-inhabited paleo and preindustrial seawaters was elucidated by applying the improved proton-controlled mechanismto biochemical reactions in cytoplasts or host tissues of marine calcifying phytoplanktons and phytosymbiont-bearing corals/zooplanktons. It was revealed that photosynthesis enhances biogenic calcificationand vice versa, as the thicker growth of CaCO3-made outer casings causes proton production and photosynthesis continuously needs protons to produce CO2(aq) from major HCO3-. The correlation between calcification and photosynthesis creates a number of stationary states with respect to oscillating pH variation. Marine biogenic calcification reaction releases no CO2 to atmosphere and is no positive feedback to rising atmospheric PCO2 levels.